2011
DOI: 10.1007/s12156-011-0082-3
|View full text |Cite
|
Sign up to set email alerts
|

Can we develop effective combination antiangiogenic therapy for patients with hepatocellular carcinoma?

Abstract: Antiangiogenic therapy has shown promise in the treatment of patients with hepatocellular carcinoma (HCC). Bevacizumab, sorafenib, and sunitinib showed efficacy in patients with HCC; and sorafenib is approved by the FDA for treatment of this cancer. In practice, the clinical benefit of these agents has been heterogeneous; and in patients who do respond, the benefit is modest and/or short-lived. Recent advances in the molecular understanding of tumor angiogenesis along with the rapid development of targeted dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…Antiangiogenic therapy prevents the initiation of neovascularization, thereby slowing tumor growth and inducing tumor regression [Folkman, 2004]. However, evidence suggests that compensatory pathways at the level of the tumor vasculature and microenvironment can promote resistance [Casanovas et al 2005;Li et al 2010;Mizukami et al 2005;Raza et al 2010;Wenger et al 2011;Yu et al 2002]. Multiple resistance mechanisms have been identified and are shown schematically in Figure 1.…”
Section: Disease Progression: Definitions and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiangiogenic therapy prevents the initiation of neovascularization, thereby slowing tumor growth and inducing tumor regression [Folkman, 2004]. However, evidence suggests that compensatory pathways at the level of the tumor vasculature and microenvironment can promote resistance [Casanovas et al 2005;Li et al 2010;Mizukami et al 2005;Raza et al 2010;Wenger et al 2011;Yu et al 2002]. Multiple resistance mechanisms have been identified and are shown schematically in Figure 1.…”
Section: Disease Progression: Definitions and Managementmentioning
confidence: 99%
“…Although recent preclinical and clinical studies have increased our understanding of the mechanisms for resistance to antiangiogenic therapy, they offer limited guidance for effective management of disease progression [Li et al 2010;Raza et al 2010;Wenger et al 2011]. In this review, we discuss key challenges in the management of HCC progression on sorafenib and review novel approaches to treatment of this patient population.…”
Section: Introductionmentioning
confidence: 99%
“…Several clinical trials have suggested that bevacizumab may be a promising agent for the treatment of advanced HCC (10,11). However, data supporting the ability of this antibody to improve the prognosis of HCC patients are insufficient at present.…”
Section: Discussionmentioning
confidence: 99%
“…Phase II clinical trials have demonstrated the efficacy of bevacizumab when used as a single agent or in combination with cytotoxic or molecular-targeted agents for the treatment of advanced HCC (10,11). The administration of bevacizumab significantly improved the survival of mice bearing human HCC tumors orthotopically transplanted in the liver (12).…”
mentioning
confidence: 99%
“…The vascular remodeling that due to pericytic over-coverage renders the neovasculature less responsive to VEGF for growth dependence effectively circumventing a blocked signaling pathway with greater dependence on other alternate mechanisms [51].…”
Section: Redundancy Of Angiogenic Signaling Pathwaysmentioning
confidence: 99%